User Perceptions of Wi-Fi Security Service in Universiti Utara Malaysia - Lubis, Arif Ridho (2012)
At the time of information technology, the development of technology runs rapidly for the needs of the users themselves. Internet access is very important to obtain any desired information around the world. As well as the internet, it develops rapidly. High mobility of the users is in need of access that can be connected all the time to the electronic device which is owned by the user. A wireless access is one of the exact solutions being applied at the present time. A security network is necessary to keep the rights of the wireless access user and security is one of the most important priorities. Security can be applied by the user or provider of communication services themselves. Because of the danger's security could be from anywhere. There are many factors that can disturb the network security. This project attempt to use the questionnaire methodology to the users of Wi-Fi in the Universiti Utara Malaysia, particularly at SOC building, to find out the perception of the users toward Wi-Fi security service provided by Universiti Utara Malaysia. All participants were SOC students with the total of 873 populations. The sample size used in this project was 109 students. The confidence level stated was 92% which represent a high confidentiality. This study found that the user aspect has a positive relation with the security aspect.